Denitration catalyst, preparation method and application thereof
By modifying zeolite and adding components such as aluminum oxide, copper salt and cerium salt, the existing denitrification catalyst problems are solved, and the efficient and high temperature-resistant denitrification effect is achieved.
Patent Information
- Application Number
- CN202311352699.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
The existing denitrification catalysts have a large loss and low service life, resulting in high costs, which limits the large-scale industrial use of SCR denitrification catalysts.
Using a denitrification catalyst composition, including zeolite, silica sol, alumina, synthetic molecular sieve, copper salt and cerium salt, through specific mixing and modification processes, the silicon-aluminum ratio and pore structure of the catalyst are enhanced, and its water resistance is enhanced. Service life.
It reduces the wear and use cost of denitrification catalysts, improves the denitrification efficiency and high-temperature resistance of the catalysts, and is suitable for high-temperature denitrification flue gases of 400-900℃.
Smart Images

Figure CN117643913B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to air pollution prevention and control materials in energy-saving and environmental protection industries, solid waste pollution disposal, resource recycling and other fields, and in particular to a denitration catalyst, a preparation method thereof, and its application in the field of high-temperature denitration. Background Art
[0002] NO x It is an important type of air pollutant, widely produced in coal-fired power plants, industrial kilns, motor vehicles, nitric acid production and many other fields. x Emission control technologies can be divided into pre-combustion removal, combustion removal and post-combustion removal. Selective catalytic reduction (SCR) is a common post-combustion removal technology with mature technology, high removal efficiency and stable system operation. It is the preferred NO removal technology at this stage. x One of the emission control measures.
[0003] However, current denitrification catalysts suffer from high losses and short service lives, which results in high costs and severely limits the large-scale industrial use of SCR denitrification catalysts. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] The present invention is expected to at least partially solve one of the above technical problems.
[0006] (II) Technical solution
[0007] In the first aspect of the present invention, a denitration catalyst composition is provided, which comprises: 30-80 parts of zeolite; 10-50 parts of silica sol; 5-30 parts of alumina; 5-30 parts of synthetic molecular sieve; 1-5 parts of copper salt; 1-5 parts of cerium salt; and 50-200 parts of water.
[0008] In some embodiments of the present invention, the zeolite is one or more of the following materials: analcime, lauzenite, phillipsite, natrolite, mordenite, heulandite, clinoptilolite, chabazite, faujasite.
[0009] In some embodiments of the present invention, the alumina is one or more of the following materials: activated alumina, including γ-Al2O3, η-Al2O3, and δ-Al2O3.
[0010] In some embodiments of the present invention, the synthetic molecular sieve is one or more of the following materials: ZSM-5, SSZ-13.
[0011] In some embodiments of the present invention, the copper salt is one or more of the following materials: copper nitrate, copper sulfate, copper acetate, copper chloride.
[0012] In some embodiments of the present invention, the cerium salt is one or more of the following materials: cerium sulfate, cerium nitrate, cerium acetate, cerium oxalate.
[0013] In a second aspect of the present invention, a method for preparing a denitration catalyst is provided. The method for preparing the denitration catalyst comprises:
[0014] Step A, stirring zeolite and silica sol, filtering and drying, calcining and then ball milling to obtain a powder 1, wherein the zeolite is 30 to 80 parts by weight and the silica sol is 10 to 50 parts by weight;
[0015] Step B, mixing powder 1 with alumina and synthetic molecular sieve in proportion and grinding to obtain powder 2, wherein the alumina is 5-30 parts by weight and the synthetic molecular sieve is 5-30 parts by weight;
[0016] Step C, adding the second powder to a solution of copper salt and cerium salt, stirring, filtering and washing, to obtain a slurry, wherein the copper salt is 1-5 parts by weight and the cerium salt is 1-5 parts by weight;
[0017] Step D: drying the slurry and separating to obtain the denitration catalyst.
[0018] In some embodiments of the present invention, in step A, the particle diameter of the zeolite is between 10 μm and 100 μm; and the stirring speed is 200 r / min to 800 r / min.
[0019] In some embodiments of the present invention, the stirring is carried out at 30°C to 60°C with heat preservation and stirring for 2h to 6h, and the calcination temperature is between 200°C and 800°C.
[0020] In some embodiments of the present invention, in step B, the grinding is room temperature ball milling, and the particle diameter of the second powder is between 10 μm and 100 μm.
[0021] In some embodiments of the present invention, in step C, stirring is performed at 30° C. to 90° C. for 2 h to 8 h, and the stirring speed is 400 r / min to 800 r / min.
[0022] In some embodiments of the present invention, in step D, drying is performed by spray granulation at a temperature of 100 to 500° C.; and / or separation is performed by separation using a cyclone separator.
[0023] In a third aspect of the present invention, a denitration catalyst is provided, which is prepared by the above preparation method.
[0024] In some embodiments of the present invention, the particle diameter is between 10 μm and 200 μm.
[0025] In a fourth aspect of the present invention, there is provided an application of the above denitration catalyst composition or denitration catalyst in the field of high-temperature denitration, wherein the high temperature is between 400-900°C.
[0026] (III) Beneficial effects
[0027] It can be seen from the above technical solution that the present invention has at least one of the following beneficial effects compared with the prior art:
[0028] (1) The main body of the denitrification catalyst is zeolite modified by silica sol and activated alumina. The synthesis process is simple, easy to industrialize, and the production cost is low.
[0029] Most of the zeolites existing in nature have a low silicon-aluminum ratio. In the present invention, the positively charged metal ions (Na2O3) on the zeolite skeleton are added by hydrothermal synthesis-high temperature calcination method without destroying the original pore structure. + ,K + , Ca 2+ Mg 2+ ) is converted into silicate, which expands the skeleton branch of zeolite, increases the silicon-aluminum ratio of zeolite, reduces the abrasion of denitration catalyst, enhances the water resistance and service life of the catalyst, and reduces the use cost of the denitration catalyst.
[0030] (2) The porous material of activated alumina, specifically at least one of γ-Al2O3, η-Al2O3, δ-Al2O3, etc., is used in combination with the pore structure of zeolite to prepare a high-temperature denitration catalyst, thereby increasing the specific surface area and pore volume of the powdered denitration catalyst, compensating for the structural defects of zeolite and increasing the acid sites.
[0031] (3) Copper and cerium elements are loaded at the same time, and denitrification is highly efficient through synergistic effect. It can be applied to high-temperature denitrification flue gas at 400-900℃. Specifically:
[0032] The copper ions are loaded to prepare the high-temperature denitration catalyst, so that the copper ions occupy a large number of cationic sites on the catalyst, and then there are more active centers and acid sites on the surface, thus enhancing the catalytic activity of the powder denitration catalyst. Site adsorption to form NH4 + , NH4 + After dehydrogenation, it forms N2 and H2O through N–N coupling with NO molecules, making the catalytic reduction reaction more thorough and the denitrification efficiency more efficient.
[0033] Copper, as an active component of the denitrification catalyst, can easily cause partial sintering of metal oxides under high-temperature flue gas, leading to blockage of the catalyst pores, so the catalytic activity under high temperature is slightly lower than that under medium and low temperature. The addition of cerium improves the oxygen-carrying capacity of the denitrification catalyst, provides sufficient oxygen for the catalytic reduction reaction under high temperature, and makes up for the defect of reduced catalytic activity of copper under high-temperature flue gas.
[0034] (4) The spray granulation process can directly atomize the slurry into tiny particles, so that the target product maintains the integrity of the microscopic surface and the uniformity of the particle diameter, reducing the filtering-drying-grinding steps in the conventional preparation process; the cyclone separation process adjusts the air volume to screen the material, and finally obtains the target product required for the test, thereby improving production efficiency, reducing labor costs, and realizing continuous operation of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The present invention is a flowchart of a method for preparing a denitration catalyst according to an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The present invention is a powder high-temperature denitration catalyst product developed for 400-900°C working conditions with the help of the existing SNCR denitration system. It is different from medium and low temperature denitration materials, and also different from high temperature liquid denitration materials.
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific implementation methods and with reference to the accompanying drawings.
[0038] According to a first aspect of the present invention, a denitration catalyst composition is provided, which comprises the following raw materials, by weight: 30-80 parts of zeolite, 5-30 parts of alumina, 5-30 parts of synthetic molecular sieve, 1-5 parts of copper salt, 1-5 parts of cerium salt, 10-50 parts of silica sol, and 50-200 parts of water.
[0039] Furthermore, the zeolite is at least one of analcime, lazurite, phillipsite, natrolite, mordenite, heulandite, clinoptilolite, chabazite, faujasite and the like.
[0040] Furthermore, the alumina is activated alumina, including at least one of γ-Al2O3, η-Al2O3, δ-Al2O3 and the like.
[0041] Furthermore, the synthetic molecular sieve is at least one of ZSM-5, SSZ-13, etc.
[0042] Furthermore, the copper salt is at least one of copper nitrate, copper sulfate, copper acetate, copper chloride, etc.
[0043] Furthermore, the cerium salt is at least one of cerium sulfate, cerium nitrate, cerium acetate, cerium oxalate, and the like.
[0044] According to a second aspect of the present invention, a method for preparing a denitration catalyst is provided. In the method for preparing the denitration catalyst, a zeolite modified by silica sol is fully mixed with alumina and a synthetic molecular sieve in proportion, copper salt and cerium salt are added, stirred, filtered, washed, and spray-dried to obtain a target product.
[0045] Figure 1 Flow chart of the method for preparing a denitration catalyst according to an embodiment of the present invention. Figure 1 As shown, the method for preparing the denitration catalyst in this embodiment includes:
[0046] Step A, after fully stirring zeolite and silica sol, filtering and drying, calcining at high temperature and then ball milling to obtain powder 1, wherein, by weight, zeolite is 30 to 80 parts and silica sol is 10 to 50 parts;
[0047] Step B, ball-milling the powder 1, activated alumina and synthetic molecular sieve in proportion, and mixing them evenly to obtain powder 2, wherein the alumina is 5-30 parts by weight and the synthetic molecular sieve is 5-30 parts by weight;
[0048] Step C, adding copper salt and cerium salt solution to the powder 2, stirring thoroughly, filtering and washing to obtain a slurry, wherein the copper salt is 1-5 parts by weight and the cerium salt is 1-5 parts by weight;
[0049] Step D: drying the slurry and separating to obtain the denitration catalyst.
[0050] In the present invention, the main body of the denitration catalyst is zeolite modified by silica sol and activated alumina, the synthesis process is simple, easy to industrialize, and the production cost of the denitration catalyst is reduced.
[0051] Each step is described in detail below.
[0052] In step A, the mass ratio of zeolite to silica sol is between 1:0.1 and 1:2. The particle diameter of zeolite powder is required to be between 10 μm and 100 μm, the stirring speed is 200 r / min to 800 r / min, the stirring is required to be kept at 30°C to 60°C for 2h to 6h, and the calcination temperature is 200°C to 800°C.
[0053] In the prior art, the role of silica sol in the preparation process of denitration catalyst is to provide silicon elements, provide channels and skeleton support for molecular sieves; or act as a binder. Different from the prior art, in the present invention, silica sol is used as a modifier to modify zeolite under high temperature calcination, breaking the original silicon-aluminum structure of zeolite:
[0054] SiO2+CaO=CaSiO3
[0055] SiO2+MgO=MgSiO3
[0056] SiO2+Na2O=Na2SiO3
[0057] SiO2+K2O=K2SiO3
[0058] Most of the zeolites existing in nature have a low silicon-aluminum ratio. In the present invention, the positively charged metal ions (Na2O3) on the zeolite skeleton are added by hydrothermal synthesis-high temperature calcination method without destroying the original pore structure. + ,K + , Ca 2+ Mg 2+ ) is converted into silicate, which expands the skeleton branch of zeolite, increases the silicon-aluminum ratio of zeolite, reduces the abrasion of denitration catalyst, enhances the water resistance and service life of the catalyst, and reduces the use cost of the denitration catalyst.
[0059] In step B, the activated alumina specifically refers to at least one of γ-Al2O3, η-Al2O3, δ-Al2O3, etc. The particle diameter of the obtained powder 2 is required to be 10 μm to 100 μm.
[0060] In the prior art, the role of activated alumina in the preparation process of denitration catalyst is to provide aluminum elements and provide pores and skeleton support for molecular sieves. Different from the prior art, in the present invention, at least one of γ-Al2O3, η-Al2O3, δ-Al2O3, etc. is used to prepare a high-temperature denitration catalyst through the porous material of activated alumina and the pore structure of zeolite, which increases the specific surface area and pore volume of the powder denitration catalyst, makes up for the structural defects of zeolite and improves the acid sites.
[0061] In step C, the mass ratio of the second powder to the copper salt is between 1:0.01 and 1:1; the mass ratio of the second powder to the cerium salt is between 1:0.01 and 1:1. In addition, the mixture needs to be stirred at 30°C to 90°C for 2h to 8h, with a stirring speed of 400r / min to 800r / min.
[0062] Among them, the copper ions are loaded to prepare the high-temperature denitration catalyst, so that the copper ions occupy a large number of cationic sites of the catalyst, and then there are more active centers and acid sites on the surface, so the catalytic activity of the powder denitration catalyst is enhanced. Site adsorption to form NH4 + , NH4 +After dehydrogenation, it forms N2 and H2O through N-N coupling with NO molecules, making the catalytic reduction reaction more thorough and the denitration efficiency more efficient. The addition of cerium improves the oxygen storage function of the denitration catalyst, providing sufficient oxygen for the denitration reaction under low oxygen conditions, ensuring the high efficiency of denitration.
[0063] It is particularly important to explain that the denitration catalyst of the present invention carries copper and cerium elements at the same time. Among them, copper element, as an active component of the denitration catalyst, is prone to partial sintering of metal oxides under high-temperature flue gas, resulting in blockage of catalyst pores, so the catalytic activity under high temperature is slightly lower than the catalytic activity under medium and low temperature. The addition of cerium element improves the oxygen-carrying capacity of the denitration catalyst, provides sufficient oxygen for the catalytic reduction reaction under high temperature, and makes up for the defect of reduced catalytic activity of copper element under high-temperature flue gas.
[0064] Through the above-mentioned synergistic effect, the activity of the denitrification catalyst at high temperature is improved, and the use temperature range of the denitrification catalyst is broadened, and it can be applied to high-temperature denitrification flue gas at 400℃-900℃.
[0065] In step D, the slurry is dried by spray granulation, and then passed through a cyclone separator to obtain powder three, i.e., the target product - denitration catalyst. The spray drying temperature is 100-500°C, and the powder at the outlet of the cyclone separator is in the form of microspheres with a particle diameter of 10-200 microns.
[0066] The spray granulation process can directly atomize the slurry into tiny particles, so that the target product maintains the integrity of the microscopic surface and the uniformity of the particle diameter, reducing the filtering-drying-grinding steps in the conventional preparation process; the cyclone separation process adjusts the air volume to screen the material, and finally obtains the target product required for the test, which improves production efficiency, reduces labor costs, and realizes continuous operation of the equipment.
[0067] According to the third aspect of the present invention, a denitration catalyst is provided. The denitration catalyst is prepared by the above preparation method. The particle diameter of the denitration catalyst is between 10 and 200 μm.
[0068] According to a fourth aspect of the present invention, there is provided a denitration catalyst composition as above, and application of the denitration catalyst in the field of high-temperature denitration, wherein the high temperature is between 400-900°C.
[0069] After actual testing, the high-temperature denitration catalyst of the present invention has a simple process, a denitration efficiency of up to 99%, and can effectively reduce ammonia escape. It can be used in many working conditions such as circulating fluidized bed boilers, waste incinerators, decomposition furnaces-rotary kilns in cement plants, and roasting furnaces in smelters.
[0070] The present invention is described in detail below with reference to specific embodiments.
[0071] Example 1
[0072] In this embodiment, the material proportions are as follows, by weight: 40 parts of zeolite, 30 parts of alumina, 20 parts of molecular sieves, 40 parts of silica sol, 2 parts of cerium salt, and 2 parts of copper salt.
[0073] The preparation method is as follows: 40 parts of zeolite and 40 parts of silica sol are stirred in a 60°C water bath for 6 hours at a stirring speed of 600 r / min, calcined in a muffle furnace at 800°C for 2 hours, ball-milled and fully mixed with 30 parts of alumina and 20 parts of molecular sieves in proportion, then 2 parts of copper salt and 2 parts of cerium salt are added and fully stirred, stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min, filtered and washed, and the slurry is fed into a spray granulator and a cyclone separator to obtain sample 1.
[0074] Example 2
[0075] In this embodiment, the material proportions are as follows, by weight: 60 parts of zeolite, 20 parts of alumina, 10 parts of molecular sieves, 30 parts of silica sol, 2 parts of cerium salt, and 2 parts of copper salt.
[0076] The preparation method is as follows: 60 parts of zeolite and 30 parts of silica sol are stirred in a 60°C water bath for 6 hours at a stirring speed of 600 r / min, and calcined in a muffle furnace at 800°C for 2 hours. After ball milling, they are fully mixed with 20 parts of alumina and 10 parts of molecular sieves in proportion, and then 2 parts of copper salt and 2 parts of cerium salt are added and fully stirred. The mixture is stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min. After filtering and washing, the slurry is fed into a spray granulator and a cyclone separator to obtain sample 2.
[0077] Example 3
[0078] In this embodiment, the material proportions are as follows, by weight: 80 parts of zeolite, 5 parts of alumina, 5 parts of molecular sieves, 40 parts of silica sol, 2 parts of cerium salt, and 2 parts of copper salt.
[0079] The preparation method is as follows: 80 parts of zeolite and 40 parts of silica sol are stirred in a 60°C water bath for 6 hours at a stirring speed of 600 r / min, and calcined in a muffle furnace at 800°C for 2 hours. After ball milling, they are fully mixed with 5 parts of alumina and 5 parts of molecular sieves in proportion, and then 2 parts of copper salt and 2 parts of cerium salt are added and fully stirred. The mixture is stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min. After filtering and washing, the slurry is fed into a spray granulator and a cyclone separator to obtain sample 3.
[0080] Example 4
[0081] In this embodiment, the material proportions are as follows, by weight: 30 parts of zeolite, 30 parts of alumina, 30 parts of molecular sieves, 50 parts of silica sol, 2 parts of cerium salt, and 2 parts of copper salt.
[0082] The preparation method is as follows: 30 parts of zeolite and 50 parts of silica sol are stirred in a 60°C water bath for 6 hours at a stirring speed of 600 r / min, and calcined in a muffle furnace at 800°C for 2 hours. After ball milling, they are fully mixed with 30 parts of alumina and 30 parts of molecular sieves in proportion, and then 2 parts of copper salt and 2 parts of cerium salt are added and fully stirred. The mixture is stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min. After filtering and washing, the slurry is fed into a spray granulator and a cyclone separator to obtain sample 4.
[0083] Example 5
[0084] In this embodiment, the material proportions are as follows, by weight: 50 parts of zeolite, 20 parts of alumina, 20 parts of molecular sieves, 50 parts of silica sol, 2 parts of cerium salt, and 2 parts of copper salt.
[0085] The preparation method is as follows: 50 parts of zeolite and 50 parts of silica sol are stirred in a 60°C water bath for 6 hours at a stirring speed of 600 r / min, and calcined in a muffle furnace at 800°C for 2 hours. After ball milling, they are fully mixed with 20 parts of alumina and 20 parts of molecular sieves in proportion, and then 2 parts of copper salt and 2 parts of cerium salt are added and fully stirred. The mixture is stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min. After filtering and washing, the slurry is fed into a spray granulator and a cyclone separator to obtain sample 5.
[0086] Comparative Example 1
[0087] In this comparative example, the material proportions are as follows, by weight: 50 parts of zeolite, 20 parts of alumina, 20 parts of molecular sieves, 2 parts of cerium salt, and 2 parts of copper salt.
[0088] The preparation method is as follows: 50 parts of zeolite, 20 parts of alumina and 20 parts of molecular sieve are fully mixed in proportion, and then 2 parts of copper salt and 2 parts of cerium salt are added and stirred thoroughly. The mixture is kept warm and stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min. After filtering and washing, the slurry is fed into a spray granulator and a cyclone separator to obtain comparative sample 1.
[0089] Comparative Example 2
[0090] In this comparative example, the material proportions are as follows, by weight: 50 parts of zeolite, 20 parts of alumina, 20 parts of molecular sieves, 50 parts of silica sol, and 2 parts of copper salt.
[0091] The preparation method is as follows: 50 parts of zeolite and 50 parts of silica sol are stirred in a 60°C water bath for 6 hours at a stirring speed of 600 r / min, calcined in a muffle furnace at 800°C for 2 hours, ball-milled and fully mixed with 20 parts of alumina and 20 parts of molecular sieves in proportion, then 2 parts of copper salt are added and fully stirred, stirred in a 90°C water bath for 4 hours at a stirring speed of 400 r / min, filtered and washed, and the slurry is fed into a spray granulator and a cyclone separator to obtain comparison sample 2.
[0092] The specific surface area and denitrification efficiency of samples 1 to 5 were tested in comparison with samples 1 to 2. The specific surface area was calculated according to the general test method in the field, and the denitrification efficiency was calculated according to the following formula:
[0093]
[0094] In actual tests, NO in flue gas x The concentration is monitored online by a flue gas analyzer, and the inlet NO x The concentration is set to 500ppm, and the outlet NO x The concentration depends on the denitration performance of the denitration catalyst sample.
[0095] The performance test data is shown in Table 1
[0096] Table 1 Performance test data of denitration catalyst samples
[0097] Sample No. <![CDATA[Specific surface area (m 2 / g)]]> Denitrification efficiency (%) Sample 1 193 95 Sample 2 184 98 Sample 3 169 91 Sample 4 178 93 Sample 5 215 97 Comparative sample 1 127 65 Comparative sample 2 135 80
[0098] Through the above-mentioned embodiments and comparative examples and performance test data, the analysis is as follows:
[0099] 1) Comparative sample 1 is a simple physical mixture of the three materials, the specific surface area is not greatly improved, and the acid sites of the catalyst cannot be effectively improved. Therefore, compared with samples 1 to 5, the specific surface area and denitrification efficiency are the lowest;
[0100] 2) Although comparative sample 2 contains silica sol-modified zeolite, it only loads copper elements. Metal oxides are easily sintered at high temperatures, resulting in partial pore blockage, which reduces the specific surface area and denitrification efficiency;
[0101] 3) Although sample 3 contains silica sol-modified zeolite and is also loaded with copper and cerium elements, the amount of activated alumina and molecular sieve added is too small, resulting in a small specific surface area and a lack of acid sites in the catalyst, thereby reducing the specific surface area and denitrification efficiency.
[0102] At this point, the various embodiments of the present invention have been introduced. According to the above description, those skilled in the art should have a clear understanding of the present invention.
[0103] It should be noted that, unless explicitly indicated to the contrary, the numerical parameters in the specification and claims of the present invention may be approximate values and may be changed according to the content of the present invention. Specifically, all the numbers indicating the content of the composition, reaction conditions, etc. recorded in the specification and claims should be understood to be modified by the term "about" in all cases, and the meaning of the expression is to include a change of ±10% from a specific number in some embodiments.
[0104] The ordinal numbers used in the specification and claims, such as "Powder 1", "Powder 2", "Powder 3", as well as Arabic numerals, letters, etc., to modify the corresponding materials (or steps), are intended only to make a material (or step) with a certain name clearly distinguishable from another material (or step) with the same name, and do not mean that the material (or step) has any ordinal number, nor do they represent the order of a certain material (or step) and another material (or step). At the same time, unless the steps are specifically described or must occur in sequence, the order of the above steps is not limited to the above list, and can be changed or rearranged according to the required design.
[0105] Those skilled in the art should understand that in the claims and description of the present invention, the word "comprising" does not exclude the existence of elements (or steps) not listed in the claims. The word "a" or "an" preceding an element (or step) does not exclude the existence of multiple such elements (or steps).
[0106] For certain implementations, if they are not the key content of the present invention and are well known to ordinary technicians in the relevant technical field, they are not described in detail in the drawings or text of the specification due to space limitations. At this time, they can be understood by referring to the relevant prior art. In addition, the purpose of providing the above embodiments is only to make the present invention meet legal requirements, and the present invention can be implemented in many different forms and should not be interpreted as limited to the embodiments described herein. In addition, the above definitions of each element and method are not limited to the various specific structures, shapes or methods mentioned in the embodiments, and ordinary technicians in this field can simply change or replace them.
[0107] Similarly, it should be understood that in order to simplify the present invention, in the above description of the exemplary embodiments of the present invention, the various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, the method of the invention should not be interpreted as reflecting the following intention: the claimed invention requires more features than the features explicitly stated in each claim. More specifically, as reflected in the claims, each inventive aspect lies in less than all the features of the previous single embodiment. Moreover, the embodiments can be mixed and matched with each other or with other embodiments based on design and reliability considerations, that is, the technical features in different embodiments can be freely combined to form more embodiments. Therefore, the claims following the specific embodiment are hereby explicitly incorporated into the specific embodiment, wherein each claim itself serves as a separate embodiment of the present invention.
[0108] The above specific embodiments provide a detailed description of the objectives, technical means and beneficial effects of the present invention. It should be understood that the purpose of the detailed description is to enable those skilled in the art to understand the present invention more clearly, and it is not used to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a denitration catalyst, characterized in that: include: Step A, stirring zeolite and silica sol, filtering and drying, calcining and then ball milling to obtain a powder 1, wherein the zeolite is 30 to 80 parts by weight and the silica sol is 10 to 50 parts by weight; The zeolite is one or more of the following materials: analcime, lazurite, phillipsite, sodium zeolite, mordenite, heulandite, clinoptilolite, chabazite, faujasite; the particle diameter of the zeolite is 10 μm to 100 μm, and the calcination temperature is 800° C. Step B, mixing powder 1 with alumina and synthetic molecular sieve in proportion and grinding to obtain powder 2, wherein the alumina is 5-30 parts by weight and the synthetic molecular sieve is 5-30 parts by weight; Step C, adding the second powder to a solution of copper salt and cerium salt, stirring, filtering and washing, to obtain a slurry, wherein the copper salt is 1-5 parts by weight and the cerium salt is 1-5 parts by weight; Step D: drying the slurry and separating to obtain a denitration catalyst.
2. The preparation method according to claim 1, characterized in that: In the step A, The stirring speed is 200r / min to 800r / min; and / or The stirring is carried out at 30°C to 60°C for 2h to 6h.
3. The preparation method according to claim 1, characterized in that: In the step B, the grinding is room temperature ball milling, and the particle diameter of the second powder is 10 μm to 100 μm.
4. The preparation method according to claim 1, characterized in that: In the step C, the stirring is carried out at 30° C. to 90° C. for 2 h to 8 h, and the stirring speed is 400 r / min to 800 r / min.
5. The preparation method according to claim 1, characterized in that: In the step D, The drying is carried out by spray granulation at a temperature of 100-500°C; and / or The separation is carried out by using a cyclone separator.
6. The preparation method according to claim 1, characterized in that: Alumina is one or more of the following materials: γ-Al2O3, η-Al2O3, δ-Al2O3; and / or The synthetic molecular sieve is one or more of the following materials: ZSM-5, SSZ-13; and / or The copper salt is one or more of the following materials: copper nitrate, copper sulfate, copper acetate, copper chloride; and / or The cerium salt is one or more of the following materials: cerium sulfate, cerium nitrate, cerium acetate, and cerium oxalate.
7. A denitration catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. The denitration catalyst according to claim 7, characterized in that: The particle diameter of the denitration catalyst is 10 μm to 200 μm.
9. Use of the denitration catalyst as claimed in claim 8 in the field of high-temperature denitration, characterized in that: The high temperature is 400°C-900°C.
Citation Information
Patent Citations
High-activity SCR molecular sieve catalyst and preparation method thereof
CN113368893A
Attrition resistant cracking catalyst
US4987110A